NaIO4-mediated selective oxidation of alkylarenes and benzylic bromides/alcohols to carbonyl derivatives using water as solvent - Ali Shaikh, Tanveer Mahammad; Emmanuvel, Lourdusamy; Sudalai, Arumugam (Journal of Organic Chemistry, 2006)
A new transition-metal-free, sodium metaperiodate (NaIO4)-mediated direct oxidation of methylarenes and benzylic bromides to the corresponding aromatic carboxylic acids is described. Under the same reaction conditions, benzylic alcohols are selectively oxidized to afford the corresponding aldehydes in good yields without undergoing overoxidation. Unprecedentedly, oxidation of benzyl bromide, toluene, or benzyl alcohol with NaIO4 underwent nuclear bromination followed by oxidation to give 4-bromobenzoic acid in 60-79% yields.